2006
DOI: 10.1103/physrevb.73.184507
|View full text |Cite
|
Sign up to set email alerts
|

Inversion techniques for optical conductivity data

Abstract: Optical data is encoded with information on the microscopic interaction between charge carriers. For an electron-phonon system, the Eliashberg equations apply and a Kubo formula can be used to get the infrared conductivity. The task of extracting the electron-phonon spectral density $\alpha^2F(\omega)$ from data is rather complicated and, thus, simplified but approximate expressions for the conductivity have often been used. We test the accuracy of such simplifications and also discuss the advantages and disad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(143 citation statements)
references
References 55 publications
9
133
0
1
Order By: Relevance
“…For optimally doped Bi-2212 with T c = 96 K the peak in the spectral density is closer to 60 meV, but Schachinger et al (2000) found that in a second Bi-2212 sample with a lower T c of 90 K from the optical data of Puchkov et al (1996), the peak was instead at 43 meV. The same value was found by Schachinger et al (2006) based on data in Bi-2212 by Tu et al (2002). To improve the quality of the sample the material used in figure 31 had some Y doping and some of the differences in the recovered spectra could be related to sample dependence.…”
Section: Tunnellingsupporting
confidence: 66%
See 1 more Smart Citation
“…For optimally doped Bi-2212 with T c = 96 K the peak in the spectral density is closer to 60 meV, but Schachinger et al (2000) found that in a second Bi-2212 sample with a lower T c of 90 K from the optical data of Puchkov et al (1996), the peak was instead at 43 meV. The same value was found by Schachinger et al (2006) based on data in Bi-2212 by Tu et al (2002). To improve the quality of the sample the material used in figure 31 had some Y doping and some of the differences in the recovered spectra could be related to sample dependence.…”
Section: Tunnellingsupporting
confidence: 66%
“…the superconducting state of our equations 12 and 21 as developed by Schachinger et al (2006). At zero temperature the appropriate kernel which replaced the kernel K(ω, Ω, T ) in equation 21 is…”
Section: Optical Propertiesmentioning
confidence: 99%
“…[33] where a maximum entropy technique is also described which allows one to recover the electron-boson spectral function I 2 χ(Ω) from a knowledge of the scattering rates 1/τ op (ω). A summary of this technique is given as follows.…”
Section: Formalismsmentioning
confidence: 99%
“…and in the superconducting state with isotropic [37,33] s-wave gap (anisotropy neglected [5,6,39]) in the clean limit by…”
Section: Formalismsmentioning
confidence: 99%
See 1 more Smart Citation